Rare ABCA7 variants in 2 German families with Alzheimer disease. (April 2018) - May, Patrick; Pichler, Sabrina; Hartl, Daniela; Bobbili, Dheeraj R.; Mayhaus, Manuel; Spaniol, Christian; Kurz, Alexander; Balling, Rudi; Schneider, Jochen G.; Riemenschneider, Matthias
Abstract : Objective: The aim of this study was to identify variants associated with familial late-onset Alzheimer disease (AD) using whole-genome sequencing. Methods: Several families with an autosomal dominant inheritance pattern of AD were analyzed by whole-genome sequencing. Variants were prioritized for rare, likely pathogenic variants in genes already known to be associated with AD and confirmed by Sanger sequencing using standard protocols. Results: We identified 2 rare ABCA7 variants (rs143718918 and rs538591288) with varying penetrance in 2 independent German AD families, respectively. The single nucleotide variant (SNV) rs143718918 causes a missense mutation, and the deletion rs538591288 causes a frameshift mutation of ABCA7 . Both variants have previously been reported in larger cohorts but with incomplete segregation information. ABCA7 is one of more than 20 AD risk loci that have so far been identified by genome-wide association studies, and both common and rare variants of ABCA7 have previously been described in different populations with higher frequencies in AD cases than in controls and varying penetrance. Furthermore, ABCA7 is known to be involved in several AD-relevant pathways. Conclusions: We conclude that both SNVs might contribute to the development of AD in the examined family members. Together with previous findings, our data confirm ABCA7 as one of the most relevant AD risk genes.